Innovation in Higher Education : Management, Needs and Challenges - Anuradha Sharma; Parineeta Jindal (New Delhi Association of Indian Universities, 2024)
Innovation is intorduced so that students learn better are instructed better and educational functions are better organised, regulated, governed and financed. The goal of management is to improve the education system. Management functions involve planning, organizing staffing, leading and controlling to ensure the best possible education outcomes by integrating theses resources Hence, using emerging technology and openness to change through education, awareness creation, and training, the level of innovation in universities and other higher education institutions increases, which in turn promotes performance and productivity. Received. Education should make the students self sufficient. With the co-operation and to holistic health. with the co-operation and understanding of stakeholders, students and faculty a seemingly convoluted task of innovation in higher education can be effectively managed and benefit many,Thus reconfiguring of education system is a journey not an endpoint
Keywords: Higher Education; Innovation; Technology; Skill Enhancement